Analisis Sektor Basis dalam Pertumbuhan Ekonomi di Kota Palopo Periode Tahun 2018-2022 - Sumantri Sumantri; Rosnina Rosnina; Suryanto Suryanto (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This study aims to analyze the leading sector or economic base in economic growth in Palopo City. This research method is descriptive quantitative using LQ analysis, Shift Share, and Klassen Typology. The data used is the PDRB of Palopo City according to business field at constant 2010 prices for the 2018–2022 period from BPS. The results showed that there were 10 (ten) basic sectors and seven non-base sectors according to business field where the LQ value was > 1. Economic growth (Dij) showed a positive value to the total value of economic performance during the period. It was concluded that most of them were in advanced sectors, potential and still able to develop rapidly because only two sectors were still relatively behind.